2012
DOI: 10.1016/j.vibspec.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated total reflectance Fourier-transform infrared spectroscopic imaging for breast histopathology

Abstract: Histopathology forms the gold standard for the diagnosis of breast cancer. Fourier Transform Infrared (FT-IR) spectroscopic imaging has been proposed to be a potentially powerful adjunct to current histopathological techniques. Most studies using FT-IR imaging for breast tissue analysis have been in the transmission or transmission-reflection mode, in which the wavelength and optics limit the data to a relatively coarse spatial resolution (typically, coarser than 5 μm × 5 μm per pixel). This resolution is insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…Diffraction-limited resolution with ATR-FTIR imaging can also be advantageous as it allows analysis of live cells in aqueous systems 21,48 . In addition, the spatial resolution of the image can be increased by incorporating optics with a high refractive index 21,34 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffraction-limited resolution with ATR-FTIR imaging can also be advantageous as it allows analysis of live cells in aqueous systems 21,48 . In addition, the spatial resolution of the image can be increased by incorporating optics with a high refractive index 21,34 .…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolution of non-aperture-based techniques is determined by the optics chosen, and it has been shown that a germanium optic is preferential, although ZnSe and diamond crystals can also be used 34 . Although transmission and transflection imaging have been widely implemented in biological tissues, imaging in ATR mode is a versatile option, because little sample preparation is required owing to minimal sample-thickness restrictions, which thus means that it has been implemented in biological fields such as pharmacology and subcellular interrogation 59,78,79 .…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of modifications that can be made to the imaging system including imaging in ATR mode 10,24,26 and using nanoscale thermal approaches 52,53 to allow for high resolution IR imaging. The main limitation with high resolution IR imaging is that the tissues must be carefully prepared and thin enough for IR to pass through (typically 4 μm thickness).…”
Section: Representative Resultsmentioning
confidence: 99%
“…, with many very exciting studies showing its applications [19][20][21][22][23][24][25] . In addition, it was recently demonstrated that the increased spatial resolution associated with ATR imaging can allow for the visualization and classification of endothelial and myoepithelial cells in breast tissue which form a key component of breast cancer diagnosis 26 . While ATR imaging is very useful, this technique requires the SIL to make contact with the tissue to form FT-IR images; therefore, its use is somewhat limited for tissue pathology where large regions of tissues must be quickly imaged.…”
Section: Introductionmentioning
confidence: 99%
“…3d that used the same NA = 0.62 objectives, but with a total magnification of 7.3x, resulting in 5.5 μm image pixels that make the basement membrane and distinction between myoepithelial and luminal epithelial cells impossible. These cells are of key histopathological interest since the destruction of the basement membrane and the disappearance of the myoepithelium are markers for invasive breast cancer 10 . …”
Section: Mammary Ductsmentioning
confidence: 99%